2015
DOI: 10.1103/physrevlett.114.247201
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in the Graphite Intercalation CompoundBaC6

Abstract: Among many two-dimensional (2D) high T(C) superconductors, graphite intercalation compounds (GICs) are the most famous intercalation family, which are classified as typical electron-phonon mediated superconductors. We show unambiguous experimental facts that BaC(6), the superconductivity of which has been missing for many years so far among various alkaline earth metal (Ca, Sr, and Ba) intercalted GICs, exhibits superconductivity at T(C)=65  mK. By adding this finding as the additional experimental point, a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…14,15 For example, various intercalated graphite compounds show enhanced superconductivity. 16,17 Our group demonstrated that K intercalation could change the electronic structures to increase the optical absorption and charge transfer efficiency, thus boosting the photocatalytic activity of g-C 3 N 4 . 18 Considering that most Bi-based layered photocatalysts have confined space, this allows heteroatoms to be doped into the interlayers.…”
Section: The Present Success In Fabricating Interlayer-i-doped Bioimentioning
confidence: 99%
“…14,15 For example, various intercalated graphite compounds show enhanced superconductivity. 16,17 Our group demonstrated that K intercalation could change the electronic structures to increase the optical absorption and charge transfer efficiency, thus boosting the photocatalytic activity of g-C 3 N 4 . 18 Considering that most Bi-based layered photocatalysts have confined space, this allows heteroatoms to be doped into the interlayers.…”
Section: The Present Success In Fabricating Interlayer-i-doped Bioimentioning
confidence: 99%
“…Various graphite intercalation compound (GIC) superconductors have been developed using liquid-metal-alloy (LMA) and vapour-transport (VT) methods12345678910111213. The highest value of the superconducting transition temperature, T c , for the GIC superconductors at ambient pressure is currently 11.5 K for CaC 6 67.…”
mentioning
confidence: 99%
“…Other than the confirmation of T c at 65 mK for BaC 6 13, the members of the GIC superconductor family have remained unchanged for the past nine years. However, we recently successfully fabricated a new series of bimetal-intercalated graphite superconductors, Ca x K 1− x C y 14.…”
mentioning
confidence: 99%
“…We present a first-principles study of the electronic band structure and low-energy dielectric response properties of a representative group of graphite intercalated compounds-LiC 6 , SrC 6 , and BaC 6 . Our results obtained from time-dependent density functional theory calculations reveal the presence of different plasmons in these compounds at energies below 12 eV.…”
mentioning
confidence: 99%
“…However, their properties vary greatly from one material to another. In LiC 6 and BaC 6 , the π plasmon is a two-dimensional excitation, whereas in SrC 6 it has a three-dimensional character. As for the intraband plasmon, it is observed in all momentum-transfer symmetry directions, with rather strong anisotropy in the energy position between momentum transfers in the basal carbon plane and perpendicular to it.…”
mentioning
confidence: 99%